EXPERIENCE IN USING LOCAL LASER HYPERTHERMIA IN MULTIMODALITY TREATMENT OF LOCALLY ADVANCED AND RECURRENT GYNECOLOGICAL TUMORS - L. N. Shevchenko; V. A. Titova; Yu. M. Kreynina; A. N. Shipilova (Опухоли женской репродуктивной системы)
To increase tumor sensitivity to specific exposure, by minimizing damage to intact tissues is an urgent task in therapy for gynecological cancer at any site. Laser-induced hyperthermia (LIHT) is a very promising effective, safety, and cost-effective technique for modify- ing a tumor response for various modalities of multimodality treatment for gynecological cancer, including for the effective therapy for locally advanced tumors and recurrences which are resistant to traditional interventions.The advantages of LIHT are firstly that it is able to regulate temperature and heating depth and volume in the real-time mode, by chang- ing the parameters of laser irradiation (wave length, power, exposure) from the data of direct thermometry used during a procedure.